ANALISIS KONSEP TAYSIR AL-NAHW MENURUT SYAUQI DHAIF DAN RELEVANSINYA TERHADAP PEMBELAJARAN NAHWU DI INDONESIA - Siska Rahayu; Hidayatul Munawaroh2; Nugroho Prasetya Adi (STAI Nusantara Kota Banda Aceh, 2026)
The teaching of Arabic grammar in Indonesia still faces various challenges, such as the complexity of the material, an overemphasis on memorizing rules, and a teaching approach that is too theoretical, making it difficult for students to master Arabic for communicative purposes. This study aims to analyze the concept of taysīr al-naḥw according to Syauqi Dhayf and to examine its relevance to the teaching of Arabic grammar in Indonesia. This study employs a qualitative approach, specifically library research, using descriptive-analytical methods. Primary data was obtained from the works of Syauqi Dhayf, particularly his book Tajdīd al-Naḥw, while secondary data was drawn from various relevant books, journals, and previous studies. Data analysis was conducted using content analysis and discourse analysis techniques. The research findings indicate that the concept of taysīr al-naḥw proposed by Syauqi Dhayf focuses on simplifying the material on Arabic grammar by reorganizing the chapters on grammar, eliminating topics deemed less functional such as i‘rāb taqdīrī and i‘rāb maḥallī as well as the reduction of topics deemed burdensome for students without providing practical benefits in the use of the Arabic language. This concept is relevant to the current state of nahwu instruction in Indonesia because it can support more effective, communicative, and language-competence-oriented learning. Nevertheless, it must be implemented in a balanced manner so as not to undermine the depth of nahwu study required for the study of classical Arabic texts and the advancement of Arabic linguistics.